The rising energy intensity of the New Zealand economy - Bertram, I.G (School of Management Working Papers, 1991)
Recently-published figures from the International Energy Agency indicate that in a world economy characterised by rising efficiency of energy use, New Zealand has been an anomaly. Between 1973 and 1988 the energy intensity ( energy required per unit of Gross Domestic Product) fell 24% for the OECD countries on average, 31 % in Japan, and 10% in Australia, whereas in New Zealand it rose 31 %. The working paper explores the New Zealand data in detail to identify the source of this behaviour and its possible causes. It is shown that the rising energy intensity of the New Zealand economy cannot be fully accounted for by reference merely to structural changes (the rise of energy-intensive petrochemicals industries, for example). Previous findings by Patterson (1989) of falling energy productivity in some sectors of the economy receive some support. Transport deregulation (including the removal of tariff protection for the local motor-vehicle and oil sectors, and the ending of regulatory restrictions on competition with Railways Corporation and Air New Zealand) clearly contributed also. Relative-price trends are shown to have provided no clear incentives to conserve energy, though other countries with strong energy-conservation records appear to have quite similar prices, suggesting that government non-price policies may have had an important effect on intensity in those countries. The very low rate of adoption of energy-saving technology in the New Zealand economy to date, coupled with clear evidence that there exist major opportunities to improve the efficiency of energy use, suggest that the time is ripe for a sharp reversal of the rising trend in New Zealand's energy intensity.